MODEL PENJAMINAN MUTU PEMBELAJARAN PADA PERGURUAN TINGGI SWASTA - Supriyanto, Eko (Jurnal VARIDIKA, 2012)
Most  of  Muhammadiyah  universities  in  specific  region  of  Yogyakarta  have  not implemented yet the quality assurance, exactly it demands both in the society and government that cannot be avoided . Therefore, this study aims to find a specific model of quality assurance in the university environment Muhammadiyah as an attempt to answer the demands in this atas. This research is qualitative research with a target of six colleges in the Muhammadiyah state uni- versities in specific region of Yogyakarta and Central Java. Those are Muhammadiyah University of Yogyakarta, University of Ahmad Dahlan, Muhammadiyah University of Magelang, Muham- madiyah University of Surakarta, Muhammadiyah University of Purworejo and Muhammadiyah University of Purwokerto. The procedure adopted to find the model of quality assurance through theoretical studies, collecting data from informants about the aspects that should be subjected to quality assurance, modeling and verification of quality assurance models. Data collection was carried out with questionnaire, interviews and documentation. Data analysis was performed with a description of the data, the analysis of flows (Flow Analysis), and contingency. The results of this study consist of two models: Model for quality assurance in learning and quality assurance models for lecturers. The  forms of quality assurance is a combination of a standard element of the quality of academic and ideologies of Muhammadiyah, while the quality assurancer are the Muhammadiyah Central Leadership, Daily Executive Agency (BPH) and the Directorate General of Higher Education. The quality assurance models found through networking opinion, in-depth interviews and document the aspects that should be subject to quality assurance to college Mu- hammadiyah Yogyakarta and Central Java. The advantages of the quality model assurance are efficiency in cost and simple in the tools and mechanism that fit to the character of Muhammadi- yah state universities. The mechanism of the model is done by committed leadership begins, then formulate the quality standards by the elements of quality assurance later implemented through institutional self-assessment and faculty independently. The development and ideology of the aca- demic community is done through the assessment.